2012
DOI: 10.5120/7623-0683
|View full text |Cite
|
Sign up to set email alerts
|

Model-driven Platform for Oil and Gas Enterprise Data Integration

Abstract: The necessity of data interoperability is very important for the oil and gas enterprise environment. Different information systems and applications cover the range of the IT infrastructure and need to interoperate. Most of the industrial companies do not have common rational strategy for their automation. That leads to the lack of integration between purchased and implemented software that is necessary for various departments. Integration problems prevent companies from building common information space. An in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…x -(Aveva, 2015b); (Aveva, 2015,p.26-30); (Aveva, 2015,p.31-33); (Aveva, 2015,p.34-37); (Aveva, 2015,p.38-39); (Aveva, 2015,p.3-5); (Aveva, 2015,p.42-45); (Aveva, 2015,p.48-51); (Aveva, 2015,p.6-9); (Bentley, 2015, p.123a x (Allan et al, 2014); (Tavallali and Karimi, 2016); (Veyber et al, 2012); (Zhang and Zhang, 2012) (Landmark, 2012); (Petex, 2014) Generate, Analyse,…”
Section: A Asset Visualisationunclassified
“…x -(Aveva, 2015b); (Aveva, 2015,p.26-30); (Aveva, 2015,p.31-33); (Aveva, 2015,p.34-37); (Aveva, 2015,p.38-39); (Aveva, 2015,p.3-5); (Aveva, 2015,p.42-45); (Aveva, 2015,p.48-51); (Aveva, 2015,p.6-9); (Bentley, 2015, p.123a x (Allan et al, 2014); (Tavallali and Karimi, 2016); (Veyber et al, 2012); (Zhang and Zhang, 2012) (Landmark, 2012); (Petex, 2014) Generate, Analyse,…”
Section: A Asset Visualisationunclassified
“…Generic solutions involves imposing standards such as [29], [30] MIMOSA, PRODML for gas and oil industry. However, authors in [36] concluded that there is no unified standard for system integration in the oil and gas industry. Another works in [37] also showed the limitations of these standards for smart gas networks.…”
Section: Discussionmentioning
confidence: 99%
“…Work has been done the electricity domain for the mapping of CIM to OPCUA [16]. However studies [17] show the limitations of these standards for smart gas networks. [17] also proposed the use of a model-based integration framework using PRODMML as the central metamodel.…”
Section: Related Workmentioning
confidence: 99%
“…However studies [17] show the limitations of these standards for smart gas networks. [17] also proposed the use of a model-based integration framework using PRODMML as the central metamodel. In contrast to these unification approaches, in our work, we seek federated interoperability solutions which do not impose the use of a centralized unified domain-specific standard.…”
Section: Related Workmentioning
confidence: 99%